2009
DOI: 10.1007/s12540-009-0671-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of material arrangement on mechanical properties in Friction Stir Welded dissimilar A5052/A5J32 aluminum alloys

Abstract: The joining of dissimilar A5052 and A5J32 alloy sheets with thicknesses of 1.5mm and 1.6mm, respectively, was carried out using the Friction Stir Welding (FSW) technique. The tool rotated at a speed in a range of 1000 rpm to 1500 rpm with a welding speed ranging from 100 mm/min to 400 mm/min. The hardness and tensile properties of the friction stir welded A5052/A5J32 joint were investigated according to the fixing location. In the case where the A5J32 aluminum alloy was fixed on the retreating side, defect-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…Niu et al [71] investigated an AA2024-AA7075 joint and found that the top section of the SZ was composed of the BM of RS, whereas the middle and bottom sections by the BM of AS as shown in Figure 5. Kim et al [65] also showed that by placing the high strength Al alloy on the AS generates excessive agglomerations and defects due to limited material flow. In essence, the high strength Al should be placed at the RS to minimize the effect of the resistance to material flow.…”
Section: Positioning Of Alloymentioning
confidence: 99%
“…Niu et al [71] investigated an AA2024-AA7075 joint and found that the top section of the SZ was composed of the BM of RS, whereas the middle and bottom sections by the BM of AS as shown in Figure 5. Kim et al [65] also showed that by placing the high strength Al alloy on the AS generates excessive agglomerations and defects due to limited material flow. In essence, the high strength Al should be placed at the RS to minimize the effect of the resistance to material flow.…”
Section: Positioning Of Alloymentioning
confidence: 99%
“…The ultimate tensile strength of the joints increases with the decrease of the heat input induced by friction. Kim et al [26] demonstrated that excessive agglomerations and defects generated by joints when the high strength Al alloy on the AS of AA5052/AA5J32 are placed due to limited flow of material. Lee et al [27] concluded that the mechanical properties of the stir zone showed higher values when AA6061 were positioned at the RS due to the complex microstructure of the stir zone.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the increase in productivity and the successful FSW joint tests presented in the literature [ 29 , 30 , 31 ], the tests were carried out at a welding speed of 300 mm/min with various rotational speeds (400, 800, 1200 rpm). At the this welding speed, defects in the form of tunnel voids and wormholes appeared regardless of the rotational speed.…”
Section: Discussionmentioning
confidence: 99%